2022
DOI: 10.3390/molecules27061967
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and Enzyme Inhibition Activities of Leaf/Bark Extracts, Fractions, Seed Oil and Isolated Compounds from Triadica sebifera (L.) Small against Aphis craccivora Koch

Abstract: Aphid, Aphis craccivora Koch (Hemiptera: Aphididae), is a major sap-sucking insect pest of leguminous crops and also transmits plant viruses, leading to economic yield loss. Indiscriminate and repeated use of insecticides for control of aphid leads to the development of resistance, and is harmful to the environment, non-target organisms, etc. Plant-based extracts/seed oils (SO) are the best alternatives to insecticides. Insecticidal activities of Triadica sebifera have not been reported against A. craccivora a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…All the concentrations of leaf and bark extract against larvae of P. xylostella in the current study showed an inhibitory effect on GST and AChE except leaf/bark extract 0.5% and seed oil 0.25%. The present results confirmed our previous studies, where the leaf, bark extract, and seed oil of T. sebifera showed significant inhibition of GST and AChE in A. craccivora [ 19 ]. The leaf extracts, seed oil, and their binary mixtures of T. sebifera showed excellent and promising antifeedant and synergistic activity against larvae of P. xylostella.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…All the concentrations of leaf and bark extract against larvae of P. xylostella in the current study showed an inhibitory effect on GST and AChE except leaf/bark extract 0.5% and seed oil 0.25%. The present results confirmed our previous studies, where the leaf, bark extract, and seed oil of T. sebifera showed significant inhibition of GST and AChE in A. craccivora [ 19 ]. The leaf extracts, seed oil, and their binary mixtures of T. sebifera showed excellent and promising antifeedant and synergistic activity against larvae of P. xylostella.…”
Section: Discussionsupporting
confidence: 92%
“…The other metabolites present in the bark ethanol aqueous extract are scopoletin, β-sitosterol, stigmasterol glycoside, kaempferitrin, and coumarin/glycosidic derivative compounds. Similarly, the deterrent activity of seed oil may be due to the presence of saturated (6.73%) and unsaturated fatty acids (26.33%) as per earlier reports [ 19 ].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations